2011
DOI: 10.1021/ie101989r
|View full text |Cite
|
Sign up to set email alerts
|

Sparger Type Influence on the Hydrodynamics of the Draft Tube Airlift Reactor with Diluted Alcohol Solutions

Abstract: The objective of this work was to investigate the influence of normal aliphatic alcohols (from methanol to n-octanol) and the gas sparger type (single orifice, perforated plate, and sinter plate) on the hydrodynamics of a draft tube airlift reactor. The results showed that the presence of alcohols led to both an increase in the gas holdup and reduction of the downcomer liquid velocity, in comparison to the values obtained in water. The type of gas sparger also changed the hydrodynamic behaviorthe gas holdup i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(128 reference statements)
1
5
0
Order By: Relevance
“…They reported that the sparger design has a noticeable effect on the gas holdup at low gas velocities (< 0.025 m s -1 ) and low solids loading (< 2 %), but only a slight effect at high gas velocities (> 0.030 m s -1 ) and high solids loading (> 3 %). Similar observations were reported by Šijački et al [7]. At lower gas velocities, they reported the highest gas holdup values in a two-phase ILAR, obtained with a sinter plate, compared to perforated-plate and single-orifice spargers.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…They reported that the sparger design has a noticeable effect on the gas holdup at low gas velocities (< 0.025 m s -1 ) and low solids loading (< 2 %), but only a slight effect at high gas velocities (> 0.030 m s -1 ) and high solids loading (> 3 %). Similar observations were reported by Šijački et al [7]. At lower gas velocities, they reported the highest gas holdup values in a two-phase ILAR, obtained with a sinter plate, compared to perforated-plate and single-orifice spargers.…”
Section: Introductionsupporting
confidence: 89%
“…To apply the model that covers the whole range of ELAR sizes (see Tab. 2), the geometrical parameter A d /A r must be included. In previous investigations, we successfully fitted experimental values with these parameters by using correlations [4,12,13,37]. The general form of the applied power law correlations was:…”
Section: Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, researchers further compared the performance of the reactors equipped with micro‐bubble spargers and millimetre‐sized bubble spargers. [ 55–58 ] Wang et al explored the differences in the mass transfer characteristics of the oxygen‐water system between the micro oxygen bubbles and millimetre‐sized oxygen bubbles in a co‐current bubble column. [ 55 ] They found that micro‐bubbles can provide a larger interfacial area in comparison to the millimetre‐sized bubbles, and therefore, the volumetric oxygen mass transfer coefficient with micro oxygen bubbles increased significantly.…”
Section: Introductionmentioning
confidence: 99%